2020
DOI: 10.1111/his.14055
|View full text |Cite
|
Sign up to set email alerts
|

Higher densities of tumour‐infiltrating lymphocytes and CD4+ T cells predict recurrence and progression of ductal carcinoma in situ of the breast

Abstract: AimsHost immunity influences cancer progression and therapeutic response. We investigated the potential of tumour‐infiltrating lymphocytes (TILs) around ductal carcinoma in situ (DCIS) in predicting recurrence and progression.Methods and resultsCD4, CD8, programmed cell death 1 (PD‐1) and programmed cell death ligand 1 (PD‐L1) expression in DCIS from 198 patients was determined by immunohistochemistry. We correlated disease‐free survival (DFS), clinicopathological parameters and biomarker expression with TIL d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 62 publications
2
29
0
Order By: Relevance
“…19 However a more recent study, which examined a cohort of 198 patients with known recurrence, demonstrated a significant association between circumferential TILs (defined as three layers of TILs surrounding ≥25% of the duct circumference) and worse disease-free survival (P = 0.012). 20 In our current study, in multivariate analysis, with adjustment for nuclear grade and necrosis, both touching TILs and circumferential TILs showed significant associations with an intermediate/ high ODX DCIS Score. Conversely, stromal TILs, which could be up to two high-power fields from the DCIS, did not show a significant association with an intermediate/high ODX DCIS Score in multivariate analysis.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…19 However a more recent study, which examined a cohort of 198 patients with known recurrence, demonstrated a significant association between circumferential TILs (defined as three layers of TILs surrounding ≥25% of the duct circumference) and worse disease-free survival (P = 0.012). 20 In our current study, in multivariate analysis, with adjustment for nuclear grade and necrosis, both touching TILs and circumferential TILs showed significant associations with an intermediate/ high ODX DCIS Score. Conversely, stromal TILs, which could be up to two high-power fields from the DCIS, did not show a significant association with an intermediate/high ODX DCIS Score in multivariate analysis.…”
Section: Discussionsupporting
confidence: 49%
“…One similar report did not find a significant association between circumferential TILs and a high ODX DCIS Score, but that study examined only 37 cases, and even in that small cohort there was a trend towards significance ( P = 0.096) 19 . However a more recent study, which examined a cohort of 198 patients with known recurrence, demonstrated a significant association between circumferential TILs (defined as three layers of TILs surrounding ≥25% of the duct circumference) and worse disease‐free survival ( P = 0.012) 20 . In our current study, in multivariate analysis, with adjustment for nuclear grade and necrosis, both touching TILs and circumferential TILs showed significant associations with an intermediate/high ODX DCIS Score.…”
Section: Discussionmentioning
confidence: 93%
“…22 Low CD8 + T cells, high FOXP3 + regulatory T cells, high numbers of B cells, and high density of CD68+ and CD163+ macrophages have been validated to be associated with increased recurrence risk in the DCIS population. 12,22,36,37 After a retrospective analysis of 117 DCIS patients, Campbell et al found that not only high cytotoxic T lymphocytes (CTL) but also high numbers of CD115 + macrophage cells were predictive of high recurrence risk. 38 A study with subset analysis of TILs has shown an association between low CD8+/FOXP3+ ratio and high risk of ipsilateral recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, they confirmed that "Touching-TILs" > 5 is an independent prognostic factor for higher ipsilateral breast tumor recurrence (IBTR). Based on different TILs evaluation criteria, many studies [22,23] have confirmed that highdensity TILs is associated with poor prognostic parameters and predicting recurrence of DCIS. Moreover, the cut-off values for the risk stratification of TILs in the current study are quite different.…”
Section: Discussionmentioning
confidence: 99%